2010
DOI: 10.1071/muv110n3_ed
|View full text |Cite
|
Sign up to set email alerts
|

The Zebra Finch: the ultimate Australian supermodel

Abstract: Abstract. Today, the Zebra Finch is Australia's most studied bird and the focus of intensive multi-million dollar research projects throughout the world. Here we briefly summarise the history of the Zebra Finch in science and document the way in which studies of this species have proliferated and dominated a number of quite different fields within the biological sciences. The importance of the Zebra Finch is likely to increase still further after the recent publication of its genome sequence -only the second b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…Taken together these results constitute the first evidence of physiological resonance solely on acoustic cues in a bird species. The zebra finch is a widely used model in biological sciences (Brainard & Doupe, 2013;Griffith & Buchanan, 2010) and its significance is likely to further increase since the publication of its genome sequence (Warren et al, 2010). The demonstration of physiological resonance and state matching in this bird offers new opportunities to study the neuronal substrates underlying the ability to detect and react to the emotional states of social partners.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together these results constitute the first evidence of physiological resonance solely on acoustic cues in a bird species. The zebra finch is a widely used model in biological sciences (Brainard & Doupe, 2013;Griffith & Buchanan, 2010) and its significance is likely to further increase since the publication of its genome sequence (Warren et al, 2010). The demonstration of physiological resonance and state matching in this bird offers new opportunities to study the neuronal substrates underlying the ability to detect and react to the emotional states of social partners.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of variability-the controlled conditions of captivity-is one of the main reasons for conducting work on research animals in the laboratory. Controlling for the high level of variation in temperature, humidity and day-length that animals are exposed to in the wild, helps us to understand fundamental questions across the range of fields that have been addressed with the captive zebra finch (Griffith and Buchanan, 2010). We note also that the studies covered in Beaulieu's (2016) commentary demonstrated effects across sets of individuals held under the same conditions, and therefore the reported differences amongst the individuals in each study are still informative.…”
Section: A Commentary Onmentioning
confidence: 99%
“…The zebra finch (Taeniopygia guttata) has become an important model species for studying the evolutionary, genomic and neural control of behaviour (Brenowitz et al 1997;Luo et al 2006;Rutstein et al 2007;Griffith and Buchanan 2010;Hauber et al 2010). The range of social behaviours, including those related to nesting and egg laying, are well characterised in this species (e.g.…”
Section: Introductionmentioning
confidence: 98%